All-polarization maintaining single-longitudinal-mode fiber laser with ultra-high OSNR, sub-KHz linewidth and extremely high stability. (September 2021) - Wang, Zhengkang; Shang, Jianming; Li, Siqiao; Mu, Kuanlin; Qiao, Yaojun; Yu, Song
Highlights: An all-PM DR-PSR-based EDFL is proposed and experimentally demonstrated. The DR-PSR serve as the efficient SLM selecting element to guarantee SLM lasing with excellent output performance. The OSNR of the EDFL is as high as 83 dB. The linewidth of the EDFL is as narrow as 459 Hz. Abstract: An all-polarization maintaining (PM) single-longitudinal-mode (SLM) erbium-doped fiber laser (EDFL) with ultra-high optical signal-to-noise ratio (OSNR), ultra-narrow linewidth and extremely high stability is proposed and experimentally demonstrated. A double-ring passive subring resonator (DR-PSR) composed of two single-coupler fiber rings and a length of unpumped EDF-based saturable absorber filter is designed and employed in the EDFL to serve as the efficient SLM selecting element to guarantee SLM lasing with excellent output performance. The all-PM structure enables the proposed EDFL to present strong ability to resist the environment disturbance. At the pump power of 100 mW, we obtain an SLM EDFL with an ultra-high OSNR of 83 dB and an ultra-narrow linewidth of 459 Hz. For the SLM operation, the all-PM EDFL processes outstanding stability performance of both the wavelength lasing and the output power. The maximum fluctuations of the center wavelength and the output power are 0.012 nm and 0.01 dB.